Analysis of Educational and Social Values in The Tradisi Sedekah Lang in the Samawa Tribe Community of West Sumbawa - Budiman; Alif Ilman Mansyur (IAIN Madura, 2022)
One of the traditions from the field of agriculture that is often carried out by the people of West Sumbawa is